Scaffolds for Knee Chondral and Osteochondral Defects: Indications for Different Clinical Scenarios. A Consensus Statement. (December 2021) - Filardo, Giuseppe; Andriolo, Luca; Angele, Peter; Berruto, Massimo; Brittberg, Mats; Condello, Vincenzo; Chubinskaya, Susan; de Girolamo, Laura; Di Martino, Alessandro; Di Matteo, Berardo; Gille, Justus; Gobbi, Alberto; et al.
Objective: To develop patient-focused consensus guidelines on the indications for the use of scaffolds to address chondral and osteochondral femoral condyle lesions. Design: The RAND/UCLA Appropriateness Method (RAM) was used to develop patient-specific recommendations by combining the best available scientific evidence with the collective judgement of a panel of experts guided by a core panel and multidisciplinary discussers. A list of specific clinical scenarios was produced regarding adult patients with symptomatic lesions without instability, malalignment, or meniscal deficiency. Each scenario underwent discussion and a 2-round vote on a 9-point Likert-type scale (range 1-3 "inappropriate, " 4-6 "uncertain, " 7-9 "appropriate"). Scores were pooled to generate expert recommendations. Results: Scaffold (chondral vs. osteochondral), patient characteristics (age and sport activity level), and lesion characteristics (etiology, size, and the presence of osteoarthritis [OA]) were considered to define 144 scenarios. The use of scaffold-based procedures was considered appropriate in all cases of chondral or osteochondral lesions when joints are not affected by OA, while OA joints presented more controversial results. The analysis of the evaluated factors showed a different weight in influencing treatment appropriateness: the presence of OA influenced 58.3% of the indications, while etiology, size, and age were discriminating factors in 54.2%, 29.2%, and 16.7% of recommendations, respectively. Conclusions: The consensus identified indications still requiring investigation, but also the convergence of the experts in several scenarios defined appropriate or inappropriate, which could support decision making in the daily clinical practice, guiding the use of scaffold-based procedures for the treatment of chondral and osteochondral knee defects.